RP-HPLC-CAD method for the rapid analysis of lipids used in lipid nanoparticles derived from dual centrifugation - Valentin Bender; Leon Fuchs; Regine Süss (Elsevier, 2024)
The use of lipids as suitable excipients for drug carrier systems has been established for years. Liposomes or lipid nanoparticles (LNPs) in general have been shown capable of delivering both hydrophilic and hydrophobic drugs. The Covid-19 pandemic and the resulting vaccines have significantly increased interest in the potential for these lipid-based systems, which can carry different types of therapeutic RNAs. LNPs used for the transfection of RNA are usually a multi-component mixture of phospholipids and other lipids. Essential components are positively charged or ionizable lipids such as DOTAP or SM-102, but also uncharged helper lipids such as cholesterol, DOPE, DSPC, DMG-PEG2000 or DSPE-PEG2000. Due to the differences in charge, simultaneous detection is a challenge. Here, we present a reversed-phase high-performance liquid chromatography charged-aerosol-detector method (RP-HPLC-CAD method) using a C-18 column for the simultaneous determination of charged and uncharged lipids. Our method has been validated according to the ICH-Q2 (R2) guideline for accuracy, precision, specificity and working range, including the limit of detection (LOD) and quantification (LOQ), as well as the calibration range. We were able to show satisfactory results in both precision and accuracy. The working range also shows great potential with a calibration range from 9.375 to 1000 μg/ml, LODs <1.85 μg/ml and LOQs <6.16 μg/ml. This method represents a fast and reproducible procedure for quantifying the lipids mentioned. In combination with the novel approach for the production of LNPs using dual centrifugation (DC), it offers the possibility of extremely rapid production of RNA-loaded LNPs, and the immediate analysis for their lipid components.